Design, Experiment, and Commissioning of the Passive Residual Heat Removal System of China’s Generation III Nuclear Power HPR1000 - Feng Li; Yazhe Lu; Xiao Chu; Qiang Zheng; Guanghao Wu (Science and Technology of Nuclear Installations)
In response to a station blackout accident similar to the Fukushima nuclear accident, China’s Generation III nuclear power HPR1000 designed and developed a passive residual heat removal system connected to the secondary side of the steam generator. Based on the two-phase natural circulation principle, the system is designed to bring out long-term core residual heat after an accident to ensure that the reactor is in a safe state. The steady-state characteristic test and transient start and run test of the PRS were carried out on the integrated experiment bench named ESPRIT. The experiment results show that the PRS can establish natural circulation and discharge residual heat of the first loop. China’s Fuqing no. 5 nuclear power plant completed the installation of the PRS in September 2019 and carried out commissioning work in October. This debugging is the first real-world debugging of the new design. This paper introduces the design process of the PRS debugging scheme.